2000
DOI: 10.1016/s1057-0810(00)00063-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk tolerance and asset allocation for investors nearing retirement

Abstract: This paper uses a large individual-level data set to isolate the effects of risk tolerance on portfolio composition. We test and confirm two predictions of the Capital Asset Pricing Model: (1) increased risk tolerance reduces an individual’s propensity to purchase risk-free assets; and (2) higher risk tolerance does not affect the composition of an individual’s portfolio of risky assets. More specifically, we find that risk tolerant investors nearing retirement do not reduce their bond all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
61
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 19 publications
9
61
0
2
Order By: Relevance
“…This positive association is in accordance with prior research (e.g., Hariharan et al 2000;Cardak & Wilkins 2009) and was also confirmed in the sensitivity analysis. Furthermore, risk tolerance was found to intervene in the relationship between financial literacy and decision-making, suggesting that less financially literate clients who tend to be less risk tolerant are more likely to allocate their funds into less risky assets.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This positive association is in accordance with prior research (e.g., Hariharan et al 2000;Cardak & Wilkins 2009) and was also confirmed in the sensitivity analysis. Furthermore, risk tolerance was found to intervene in the relationship between financial literacy and decision-making, suggesting that less financially literate clients who tend to be less risk tolerant are more likely to allocate their funds into less risky assets.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, it has been reported that risk tolerant individuals tend to invest less in risk free assets (Hariharan et al 2000) or risk averse households are more likely to have a lower proportion of their assets allocated in risky assets (Cardak & Wilkins 2009). Consistent with these studies, it is logical to expect (H7) that risk tolerant clients tend to invest in riskier products compared to less risk tolerant ones.…”
Section: Financial Risk Tolerance and Investment Decision-making (H7)mentioning
confidence: 76%
See 2 more Smart Citations
“…For instance, it is seen that individuals with high levels of financial risk tolerance prefer stocks rather than bonds and certificates of deposit in their retirement funds (Hariharan et al, 2000). Van Rooij et al (2007) investigated risk attitudes towards general matters, financial matters and pension matters and found that for the decisions regarding the pension, individuals acted in the most risk-averse manner choosing the most conservative portfolios of funds.…”
Section: Financial Risk Tolerancementioning
confidence: 99%